Postoperative administration of dienogest for suppressing recurrence of disease and relieving pain in subjects with ovarian endometriomas. (2nd August 2016) - Adachi, Kazushige; Takahashi, Kayo; Nakamura, Koji; Otake, Akiko; Sasamoto, Naoko; Miyoshi, Yukari; Shioji, Mitsunori; Yamamoto, Yoshimitsu; Fujitani, Mayumi; Wakimoto, Akinori; Tokuhira, Atsushi; Kobayashi, Eiji; et al.
Abstract: To assess the effect of dienogest on recurrence of ovarian endometriomas and severity of pain after laparoscopic surgery, a retrospective study of 81 patients was performed at three institutions in Osaka, Japan. Patients had a six-month minimum follow-up after laparoscopic surgery for ovarian endometriomas performed between June 2012 and August 2014. Patients who chose to receive 2 mg dienogest daily and those who were managed expectantly postoperatively were included. Recurrence was defined as the presence of endometriomas of more than 2 cm. A visual analog scale (VAS) was used to score the intensity of pelvic pain. The cumulative recurrence rate and absolute VAS score changes between the baseline and at 6, 12, 18 and 24 months after the start of administration were evaluated in both groups. The recurrence rate was 16.5% and 24.0% in the expectant management group at 12 and 24 months, respectively. No recurrences occurred in the dienogest treatment group. The rate of VAS score reduction was significantly higher in the dienogest than in the expectant management group. Dienogest is effective on the recurrence of ovarian endometrioma and relieving pelvic pain after laparoscopic surgery.